Assessment of Appropriateness in Glucocorticoid Prescribing in Medicine In-patients: AProspective Observational Study - R, Asawari; P, Atmaram; G, Kushal; T, Aeyna (Indian Journal of Pharmacy Practice)
The purpose of this study was to assess the appropriateness in glucocorticoid prescribing with respect to selection, dose, duration and route of therapy to prevent therapeutic failure or occurrence of glucocorticoid associated adverse effects. Aprospective observational study was conducted at tertiary care teaching hospital for the duration of 5 months. Patient's medical records were reviewed for patient demographics and pattern of glucocorticoid therapy prescribed. The data so obtained were analyzed to that of the recommended treatment guidelines. In our study, it was found that with respect to selection of glucocorticoid therapy, 80% were prescribed appropriately while 20% were inappropriately prescribed. As per doses, 43.75% of glucocorticoids were found appropriate while 53.13% and 3.13% were prescribed under dosage and in over dose respectively. According to duration 53.13% glucocorticoids prescribed inappropriately. All the glucocorticoids were prescribed appropriately according to the route of administration. To conclude, this study might be useful to alert health care professionals regarding the inappropriate prescribing of glucocorticoids and its consequences.
Keywords: Appropriate; Selection; Therapeutic deviation; Hyperglycemia